2013
DOI: 10.1016/j.amjmed.2012.05.029
|View full text |Cite|
|
Sign up to set email alerts
|

Cognitive Impairment in Older Adults with Heart Failure: Prevalence, Documentation, and Impact on Outcomes

Abstract: Background Despite the fact that 80% of patients with heart failure are over age 65, recognition of cognitive impairment by physicians in this population has received relatively little attention. The purpose of our study was to evaluate physician documentation (as a measure of recognition) of cognitive impairment at time of discharge in a cohort of older adults hospitalized for heart failure. Methods We performed a prospective cohort study of older adults hospitalized with a primary diagnosis of heart failur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
169
1
8

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(186 citation statements)
references
References 39 publications
8
169
1
8
Order By: Relevance
“…2,6,8,10,22,23 A twofold increase in 30-day death and readmissions, 8 almost fivefold rates of 1-year mortality, 23 as well as increase in hospitalisation and/or death within 5 years were demonstrated. 22 Such association with poor outcomes is observed even in cases of mild CI, 8 which frequently remains undiagnosed.…”
Section: Importance Of Cognitive Decline For Prognosis and Self-carementioning
confidence: 95%
See 2 more Smart Citations
“…2,6,8,10,22,23 A twofold increase in 30-day death and readmissions, 8 almost fivefold rates of 1-year mortality, 23 as well as increase in hospitalisation and/or death within 5 years were demonstrated. 22 Such association with poor outcomes is observed even in cases of mild CI, 8 which frequently remains undiagnosed.…”
Section: Importance Of Cognitive Decline For Prognosis and Self-carementioning
confidence: 95%
“…Reported prevalence [2][3][4][5][6][7][8] of cognitive dysfunction in the heart failure (HF) population parallels the severity of HF, being the highest in the acute decompensation settings (see Table 1). …”
Section: Prevalence and Pathogenic Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…72 A prospective cohort study of older adults hospitalized with a primary diagnosis of HF showed that patients with moderate-severe cognitive impairment were significantly more likely to die or be readmitted to hospital at 6 months compared with patients with no impairment (adjusted HR, 1.60; 95% CI, 1.03-2.48; P=0.04). 73 The substudy of the Trial of Intensified vs. standard Medical therapy in Elderly patients with Congestive Heart Failure (TIME-CHF) also reported that severe cognitive impairment was related to higher mortality (HR 1.53, 95% CI 1.02-2.30, P=0.04). 74 …”
Section: Impaired Cognitive Function During Hfmentioning
confidence: 99%
“…42 Patients with decompensated HF can experience difficulty with short-term memory, working memory, executive control and processing speed. Executive dysfunction and memory problems interfere with self-care and problem-solving, though many patients seemingly converse normally despite moderate-tosevere impairment.…”
Section: Cognitive Impairments With Heart Failurementioning
confidence: 99%